Evaluation of Post-resuscitation Care Practices of Physicians Working in Intensive Care Units - Ozcan, Sibel; Birbicer, Handan; Karaaslan, Pelin; Keles, Gonul Tezcan; Karahan, Mahmut Alp (Galenos Publ House, 2024)
Objective: In this study, it was aimed to evaluate the practices of physicians working in intensive care units about post-resuscitation care in patients whose spontaneous circulation returned with cardiopulmonary resuscitation. Materials and Methods: In this cross-sectional study, a web-based questionnaire containing 28 questions was applied to physicians working in an intensive care units. Results: A total of 118 specialist physicians participated in the study. The mean arterial pressure target after resuscitation was mostly (91.5%) 65-75 mmHg, and the most preferred inotropic agent was noradrenaline (81.2%). It was determined that 52.1% of the participants applied targeted temperature management and continued for 24 h. Neuroprognostic evaluation was performed after 24 h, and most commonly Glasgow coma scale (96.6%), pupillary and corneal reflexes (92.2%), and computerized brain tomography (60.3%) were used. However, it was observed that biomarkers and neurophysiological methods were used less frequently. Conclusion: In this study, it was observed that there were differences in practices according to hospital conditions in post-resuscitation care, but physicians generally followed international guidelines. Simultaneously, it is considered that in addition to the international guidelines, national guidelines are necessary in accordance with the conditions of our country, and training was needed for standard applications.
Keywords: Intensive care; post-resuscitation care; questionnaire